Manajemen Kurikulum di Madrasah: Tantangan dan Peluang dalam meningkatkan mutu pendidikan - Isroful Jannah; Ahmad Royani; Siti Baro'ah (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2026)
Curriculum management plays a strategic role in improving the quality of education in madrasahs. A curriculum that is managed systematically and sustainably is key to responding to changes in education and meeting students’ needs. This article aims to analyze curriculum management in madrasahs by highlighting the challenges and opportunities in improving educational quality. The research method used is library research, which involves examining relevant literature such as books, scholarly journal articles, and educational policy documents. The findings indicate that the main challenges in curriculum management in madrasahs include limitations in human resources, teachers’ readiness to implement the curriculum, and the harmonization between the national curriculum and the characteristics of Islamic education. On the other hand, madrasahs have significant opportunities through the strengthening of Islamic values, the development of innovative learning practices, and the enhancement of educators’ professionalism. With the implementation of effective, well-planned, and contextual curriculum management, madrasahs have the potential to improve learning quality and educational outcomes in a sustainable manner. This study is expected to serve as a conceptual reference for madrasah administrators in developing curriculum management that is adaptive to the dynamics of education.